Rescue of Replication-Competent ZIKV Hidden in Placenta-Derived Mesenchymal Cells Long After the Resolution of the Infection. (9th October 2019) - Bordoni, Veronica; Lalle, Eleonora; Colavita, Francesca; Baiocchini, Andrea; Nardacci, Roberta; Falasca, Laura; Carletti, Fabrizio; Cimini, Eleonora; Bordi, Licia; Kobinger, Gary; D'Ambrosio, Valentina; Natale, Fabio; et al.
Abstract: The Zika virus (ZIKV) genome, its negative-strand viral proteins, and virus-like particles were detected in placenta-derived mesenchymal cells (MSCs), indicating that ZIKV persists after virus clearance from maternal blood and can be rescued by in vitro cultivation. We report for the first time the presence of replication-competent ZIKV in MSCs from an asymptomatic woman who acquired infection during pregnancy. Abstract : Replication-competent ZIKV was rescued from placenta-derived mesenchymal cells (MSCs), isolated from a woman who acquired the infection during pregnancy, cleared viremia and delivered a newborn with no signs of infection. Our findings suggest a possible role of placental MSCs as ZIKV reservoir in vertical transmission.